Pd supported on Ti-suboxides as bifunctional catalyst for air electrodes of metal-air batteries. (16th November 2016) - Alegre, C.; Modica, E.; Lo Vecchio, C.; Siracusano, S.; Aricò, A.S.; Baglio, V.
Abstract: Bifunctional air electrodes catalysing both the oxygen reduction and oxygen evolution reactions are essential in electrochemical devices such as metal-air batteries and regenerative fuel cells. Unfortunately, highly positive electrochemical potentials take place at the positive electrode (air electrode) especially during the oxygen evolution reaction. This is a highly corrosive condition and, thus, more stable catalysts are required. In the present work, titanium suboxides (Tin O2n−1 ) have been studied as palladium catalyst support for the air electrode of metal-air batteries. The performance of Pd/Tin O2n−1 towards both the oxygen reduction and the oxygen evolution reactions in alkaline media was analysed. Besides, the stability of the catalysts was assessed by subjecting them to accelerated stress tests. These catalysts were compared to a Pd catalyst supported on a conventional carbon black (Vulcan). Pd/Tin O2n−1 showed a suitable activity as bifunctional catalyst, comparable to Pd/Vulcan, particularly for the ORR. Besides, it showed a higher performance with time than the carbonaceous support-based catalyst when subjected to harsh electrochemical conditions (1.8 V vs. RHE for 8 h). This indicates a more suitable stability for application in metal-air batteries. Highlights: Ti-suboxides were studied as Pd support for air electrodes of metal-air batteries. The performance of Pd/Tin O2n−1 for ORR and OER in alkaline media was analysed. Pd on titanium-suboxides proved to be an effective bifunctional catalyst. Pd/Tin O2n−1 showed suitable stability for metal-air batteries.